Peningkatan Motivasi dan Tanggung Jawab Belajar berbasis Project Based Learning (PJBL) dalam Memahami Karya Ilmiah kelas XI SMA Negeri 3 Palembang - Ristika, Ria; Lestari, Hikmah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to increase the learning motivation and learning responsibility of class XI students at SMA Negeri 3 Palembang in understanding scientific work through the implementation of the Project Based Learning (PJBL) method. The problem identified was students' low learning motivation and learning responsibility, which was reflected in passive participation, lack of interest in the material, and limited level of understanding. Data from observations and questionnaires were analyzed using percentage calculations. This research was carried out in two cycles. The results of the research show an increase in students' motivation and responsibility in project assignment-based learning.